Experimental determination of static and dynamic Young’s moduli of healthy and degenerated bovine articular cartilage using the split-Hopkinson pressure bar - Takahiro MORI; Hiroto SAKURAI; Koichi KOBAYASHI; Makoto SAKAMOTO; Yuji TANABE (Mechanical Engineering Journal, 2022)
Osteoarthritis (OA) is a disease in which articular cartilage wears down due to degeneration associated with aging, which makes adjacent bones contact each other and causes pain. Considering that OA changes the mechanical properties of cartilage when it degenerates, it is important to investigate its mechanical properties under impact load. Therefore, in this study, dynamic and quasi-static tests using the split-Hopkinson pressure bar (SHPB) were carried out on healthy cartilage and cartilage with collagen fibers degenerated by enzyme treatment. The differences in elastic moduli over a wide range of strain rates were examined. To obtain the mechanical properties of soft tissue, polymethyl methacrylate was used for the input and output bars of the SHPB because of its low mechanical impedance, which is suitable for highly compliant materials. Healthy and degenerated cartilage specimens were prepared to clarify the difference in mechanical properties, and quasi-static compression and SHPB tests were performed. The results showed that the elastic modulus increased with increasing strain rate, revealing that the strain rate dependency affects both healthy and degenerated articular cartilage. However, in the high-strain-rate region, a significant positive correlation was observed in healthy cartilage, but no correlation was observed in degenerated cartilage. This suggests that, in degenerated cartilage, resistance to static and dynamic loads, as well as viscosity, decreased at a high strain rate. According to the biphasic theory, the higher the strain rate is, the more it tends to limit interstitial water flow, which explains the increase in elastic modulus in the high-strain-rate region. Therefore, these results suggest that degeneration of collagen fibers in the cartilage reduces the resistance to internal water flow and to static and dynamic loads.